2015
DOI: 10.1111/sji.12312
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐33 Triggers B1 Cell Expansion and Its Release of Monocyte/Macrophage Chemoattractants and Growth Factors

Abstract: B1 B lymphocytes are natural IgM-producing cells primarily found in peritoneum and mucosal sites. They perform vital functions during the early defence against viral and bacterial infections. Murine B1 cells express IL-33 receptor complex on activation. IL-33 is a new addition to the IL-1 family with a strong role in Th2 immunity. B1 cells have been recognized to exacerbate contact sensitivity by producing IgM and IL-5 in response to interleukin-33. However, the exact response of IL-33/ST2 signalling in B1 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
0
16
0
1
Order By: Relevance
“…In mice, IL-33 enhances immunoglobulin (Ig)M synthesis and markedly induces and activates B1 cells in an ST2-dependent manner [18]. Additionally, IL-33 could also induce regulatory B cells to produce IL-10, attenuating mucosal inflammation in the gut [19].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, IL-33 enhances immunoglobulin (Ig)M synthesis and markedly induces and activates B1 cells in an ST2-dependent manner [18]. Additionally, IL-33 could also induce regulatory B cells to produce IL-10, attenuating mucosal inflammation in the gut [19].…”
Section: Introductionmentioning
confidence: 99%
“…Others have described the ability of IL‐33 to induce the proliferation of B1‐cells, a cell population that makes up a large proportion of the immune cells within the serous cavities . More recently, it has been shown that sorted B1b cells placed into culture with IL‐33 will secrete CSF2 (GM‐CSF) which leads to the alternative possibility that IL‐33 may induce CSF2 from B‐cells within the serous cavities, which then contribute to the proliferation of resident serous macrophages. Future experiments will be required to determine whether the action of IL‐33 on macrophages requires cell‐intrinsic expression of the IL‐33R and whether there is requirement for B‐cell derived CSF2 in the IL‐33 driven macrophage proliferation system.…”
Section: Discussionmentioning
confidence: 99%
“…Komai-Koma et al recently showed that B1 cells proliferate after daily i.p. injection with IL-33 ( Komai-Koma et al, 2011 ) through production of IL-5 that then upregulated ST2 on B1 cells ( Ahmed and Koma, 2015 ). To test the effect of IL-33 on B1 cell IgE production, we injected IL-33 i.p.…”
Section: Resultsmentioning
confidence: 99%